HAK PEKERJA YANG MENGALAMI PEMUTUSAN HUBUNGAN KERJA BERDASARKAN PERATURAN PEMERINTAH NOMOR 35 TAHUN 2021 - Rahmawati Kusuma; AD Basniwati (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
This study aims to determine the rights of workers who experience termination of employment based on Government Regulation No. 35 of 2021 concerning certain time work agreements, outsourcing, work and rest periods, and termination of employment. This research uses normative legal research by using approach methods, namely; Legislation approach method, conceptual approach and Historical approach. The analysis of legal materials obtained is in accordance with the above data collection techniques, then the collected data is then processed and analyzed qualitatively. The results of the research and discussion conclude that the regulation regarding the process of termination of employment as regulated in Articles 37,38 and 39 as well as the rights of workers obtained in the event of termination of employment are contained in Articles 40 to 59 of Government Regulation Number 35 of 2021 concerning work agreement for a certain time, outsourcing, working time and rest time, and termination of employment.